Entrepreneurial Intention Among Students: The Effect of Self-efficacy and Entrepreneurial Attitude - Nursyirwan, Vivi Iswanti; Purwana, Dedi; Suhud, Usep; Harahap, Irwan Leo Putra; Valentika, Nina (Faculty of Economics, Universitas Negeri Indonesia,Indonesia, 2022)
To escalate the number of university students’ entrepreneurs, it is important to understand the role of self-efficacy and entrepreneurial attitude. The goal of this study is to investigate the role of self-efficacy in influencing students’ entrepreneurial attitudes and intentions. This study also examines the effect of entrepreneurial attitudes linked with students’ entrepreneurial intentions. The study used a cross-sectional survey design with a purposive sample of 100 university students at Universitas Pamulang in Indonesia. Structural Equation Modeling-Partial Least Square (SEM-PLS) is used to the connectivity among the independent–dependent variables in the research. The results of the study found that entrepreneurial self-efficacy had a significant positive effect on the entrepreneurial intentions of university students. In addition, attitudes towards entrepreneurship have a significant positive effect on entrepreneurial intentions. Indeed, entrepreneurial self-efficacy has a positive effect on attitudes towards entrepreneurship, and a significant influence is obtained between entrepreneurial self-efficacy on entrepreneurial intentions and attitudes towards entrepreneurship as an intervening variable